2021
DOI: 10.3126/njb.v9i1.38671
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual Property Right on Basmati Rice: Current Scenario and Evidences of Origin, Diversity, Cultivation and Use Values of Basmati Rice in Nepal

Abstract: Basmati rice, also called the king/prince of rice landraces has very special values in Nepalese society as well as in other countries of Indian Subcontinent. With the objectives of collecting, analyzing and documenting Basmati related information in Nepal, we visited different sites; carried out key informant surveys; organized focus group discussions, online interaction and discussion meetings; requested all relevant offices/ persons/ stakeholders through phone, website, and letter to share information; organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Anadi, the only glutinous (sticky) variety native to the middle hills of Nepal was selected for its special food value, and supposed nutritional and medicinal value (Sthapit et al, 2005). Kalo Nuniya/Kalo Nunia was chosen for its aromatic property (CDD, 2015;Joshi et al, 2021), popularity, high cultural-, social- (Joshi et al, 2020) and market-value (Adhikari et al, 2017). Bhotange rice landrace was selected to properly document, promote and assess the relevant quality parameters, thereby providing further scope for quality breeding and its conservation as the literature regarding this landrace remains very scanty.…”
Section: Introductionmentioning
confidence: 99%
“…Anadi, the only glutinous (sticky) variety native to the middle hills of Nepal was selected for its special food value, and supposed nutritional and medicinal value (Sthapit et al, 2005). Kalo Nuniya/Kalo Nunia was chosen for its aromatic property (CDD, 2015;Joshi et al, 2021), popularity, high cultural-, social- (Joshi et al, 2020) and market-value (Adhikari et al, 2017). Bhotange rice landrace was selected to properly document, promote and assess the relevant quality parameters, thereby providing further scope for quality breeding and its conservation as the literature regarding this landrace remains very scanty.…”
Section: Introductionmentioning
confidence: 99%
“…The coarse and medium rice varieties cover almost 76% and medium fine and fine rice varieties share 17% and 7% of the total milled rice respectively in Nepal (Joshi et al, 2020;NAPREC, 2021). Joshi et al (2021) reported that total 133 basmati type rice also called aromatic rice landraces are grown in 60 districts of Nepal and only four basmati type of rice landraces have been registered in National Seed Board. The aromatic rice is highly reputed and very costly.…”
Section: Introductionmentioning
confidence: 99%
“…Nepal used to export rice including aromatic rice before 1980 (Joshi et al, 2021;Mallick 1981;Gauchan, 2002) to India, China, Singapore and Bangladesh. However, changing rice consumption behavior led to a high demand of rice.…”
Section: Introductionmentioning
confidence: 99%